Two-voxel spectroscopy with dynamic B0 shimming and flip angle adjustment at 7 T in the human motor cortex - Lemke, C; Hess, A; Clare, S; Bachtiar, V; Stagg, C; Jezzard, P; Emir, U (Wiley, 2015)
The aim of this study was to acquire high-quality in vivo (1) H spectra concurrently from two voxels at ultra-high field (7 T) without specialized hardware. To this end, an acquisition scheme was developed in which first-order shims and flip angles are dynamically updated to acquire spectra from both of the brain's motor cortices in an alternating fashion. To validate this acquisition scheme, separate, static, single-voxel acquisitions were also performed for comparison. Six subjects were examined using semi-LASER spectroscopy at 7 T. Barium titanate pads were used to increase the extent of the effective transmit field (B1 (+) ). Spectra were obtained from the hand area of both motor cortices for both acquisition schemes. LCModel was used to determine neurochemical profiles in order to examine variations between acquisition schemes and volumes of interest. The dynamic two-voxel acquisition protocol produced water linewidths (full width at half-maximum between 11.6 and 12.8 Hz) and signal-to-noise ratios similar to those from static single-voxel measurements. The concentrations of 13 individual and 3 combined metabolites with Cramér-Rao lower bounds below 30% were reliably detected for both acquisition schemes, and agreed well with previous postmortem assay and spectroscopy studies. The results show that high spectral quality from two voxels can be acquired concurrently without specialized hardware. This practical technique can be applied to many neuroscience applications.